Education as a Pillar of Management Development in Healthcare - Lukhanin, Oleksandr; Šprajc, Polona; Lukhanina, Yuliia (Management skozi prizmo digitalnega in zelenega prehoda v družbo 5.0, 2025)
Management is one of the basic pillars of any organization, whether public or private, and the specificities of management are linked to healthcare management. Often, the leaders and managers of healthcare institutions are excellent professionals but lack soft skills in the area of employee management. Similarly, managers, although experienced in different organizations, find it difficult to manage the healthcare environment because they have little or no medical health background. We see the presence of qualified, adequately motivated health personnel as one of the main factors for the successful development and functioning of the health care system, strengthening the capacity of the public health system to meet the needs of the population, and being prepared for emergencies and responding appropriately to modern situations. To improve the quality and accessibility of health care for the population, staffing problems in the health system need to be addressed, linked to further improvements in the processes of planning, training, and deployment of health personnel. Training of managers at all levels is key to success in achieving healthcare management objectives.